Identification and classification of power quality disturbances using MATLAB analysis / Noor Suhana Mohd Zubir - Mohd Zubir, Noor Suhana (2006)
This project will briefly discuss the use of Discreet Wavelet Transform Analysis (DWT) in attempt to determine power disturbances according to the appearances of resulting waveforms. By combining the methods of filtering Wavelet Analysis and Artificial Neural Network (ANN) in order to characterize and classify of power disturbances in the transmission system. These programs were developed using MATLAB version 7.0.